1996
DOI: 10.1177/112067219600600302
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cryopreservation of Human Donor Corneas

Abstract: The purpose of the present study was to develop an optimal freezing method for cryopreservation of human donor corneas for transplantation. Three groups of ten human donor corneas each were cryopreserved using cooling rates of 0.5 degree C/ min, 1 degree C/min and 9 degrees C/min. The freezing medium contained 10% fetal calf serum and 7% dimethylsulphoxide. Ten additional human donor corneas were used as controls. Endothelial cell survival after complete thawing was assessed by calculating the mean endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…It is important to stress that the interpretation of our study is based upon the use of primary aortic endothelial cells from multiple donors. Previous reports have shown interindividual variability (Canals et al ., 1996; Rice et al ., 1996) and heterogeneity within the vasculature of the same organ (Antonov et al ., 1986; Ghitescu and Robert, 2002) in experiments conducted utilizing primary endothelial cells. We observed some variability in the amounts of chemokine and cytokine produced in response to the various stimuli employed in this study; however, similar trends were observed in the results from all donors.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to stress that the interpretation of our study is based upon the use of primary aortic endothelial cells from multiple donors. Previous reports have shown interindividual variability (Canals et al ., 1996; Rice et al ., 1996) and heterogeneity within the vasculature of the same organ (Antonov et al ., 1986; Ghitescu and Robert, 2002) in experiments conducted utilizing primary endothelial cells. We observed some variability in the amounts of chemokine and cytokine produced in response to the various stimuli employed in this study; however, similar trends were observed in the results from all donors.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Delbosc et al [1984] and Böhnke et al [1986] describe endothelial cell necrosis phenomena and enlargement of intercellular spaces in human cryopreserved corneas. Canals et al [1996] calculate 12.2% dead endothelial cells in human corneas cryopreserved at 1¤°C/min in 7% dimethylsulfoxide.…”
Section: Discussionmentioning
confidence: 99%
“…A maximum postthawing endothelial cell survival of 90% was achieved when using 7% dimethylsulphoxide, a 1¤°C/min cooling rate and thawing in a water bath at 37¤°C. The cryopreservation process used in the present study has also been tested in human corneas at different cooling rates, showing optimum results when using a 1¤°C/min cooling speed [Canals et al, 1996].…”
Section: Cryopreservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been reported on cryoprotection of porcine cornea in dextran and Me 2 SO of concentrations higher than those used in our experimental system (Canals et al, 1996;Wusterman et al, 1999). The human cornea has been shown to successfully recover from freezing cryoprotected in Me 2 SO (Canals et al, 1999), Me 2 SO, formamide and 1,2-propanediol , Me 2 SO, glycerol and 2,3-butanediol .…”
Section: Discussionmentioning
confidence: 99%